2021
DOI: 10.3390/pr9020352
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Metal Recovery from MSWI Fly Ash by Acid Leaching: Findings from Laboratory- and Industrial-Scale Experiments

Abstract: A major part of Swiss fly ashes (FA) from municipal solid waste incineration (MSWI) are treated with the acid fly ash leaching process (FLUWA) in order to recover heavy metals prior to deposition. The FLUWA process uses scrub water from wet flue gas cleaning to leach heavy metals from FA. The leaching efficiency is strongly dependent on the leaching conditions (e.g., pH, Eh, L/S-ratio). This case study presents the optimization of the FLUWA process at the MSWI plant Linth, Switzerland, through determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previously there have been only a few studies of the radioactivity of waste incineration residues internationally [5][6][7][8], and no studies in Finland. Due to the levels of heavy metals in the residues [9,10] the beneficial use of waste incineration residues can be limited, but as advanced forms of reuse and recycling are developed, such as more efficient metals recovery [11], it is also important to investigate and document the levels of radionuclides in the residues. For this purpose, in this study the residues from nine waste incineration plants in Finland were characterised for natural and artificial radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…Previously there have been only a few studies of the radioactivity of waste incineration residues internationally [5][6][7][8], and no studies in Finland. Due to the levels of heavy metals in the residues [9,10] the beneficial use of waste incineration residues can be limited, but as advanced forms of reuse and recycling are developed, such as more efficient metals recovery [11], it is also important to investigate and document the levels of radionuclides in the residues. For this purpose, in this study the residues from nine waste incineration plants in Finland were characterised for natural and artificial radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several techniques, mainly of a thermal or hydrometallurgical nature [51], are under study. The greatest economic potential likely lies in the integration with other operations conducted at the WtE plant: for instance, zinc recovery via acid leaching by reusing effluents from wet flue gas cleaning systems, of which the feasibility at an industrial scale was demonstrated recently [52,53].…”
Section: Valorization Of Bottom and Fly Ash From Conventional Wte Ope...mentioning
confidence: 99%
“…Therefore, nearly all MSW incineration FA (MSW-FA) is stabilized/solidified and deposited as toxic waste in landfills, and due to their enormous volumes, taking up valuable space. However, a shift in focus from environmental impacts to resource recovery has identified the potential value of embedded salts and metals in the MSW-FA, and some progress has been made in recovering these resources [5][6][7].…”
Section: Introductionmentioning
confidence: 99%